2019
DOI: 10.33545/surgery.2019.v3.i3d.168
|View full text |Cite
|
Sign up to set email alerts
|

Continuous low dose antibiotic prophylaxis versus no antibiotics with respect to urinary tract infection and biofilm formation in the patients with double-j stents: A prospective randomized study

Abstract: Objective: To evaluate effects of Continuous low dose antibiotic prophylaxis versus no antibiotics in the patients with DJ stents with respect to urinary tract infection (UTI and biofilm formation. Material and Methods: A prospective randomized study in 36 patients being stented for stone disease, pelvi-ureteric junction obstruction (PUJO), were divided into 2 groups. Group 1 containing 18 patients received T. Nitrofurantoin 100mg once a day after stenting and Group 2 containing 18 patients received no antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Our study has similar rate of urine culture and DJ stent culture positivity as a study by Kehinde et al 3 In a recent Study by Desai et al found no difference in urine culture and DJ stent culture positivity rate when compared no antibiotic versus continuous antibiotic prophylaxis in DJ stented patient which is similar to our study results. 11…”
Section: Discussionmentioning
confidence: 99%
“…Our study has similar rate of urine culture and DJ stent culture positivity as a study by Kehinde et al 3 In a recent Study by Desai et al found no difference in urine culture and DJ stent culture positivity rate when compared no antibiotic versus continuous antibiotic prophylaxis in DJ stented patient which is similar to our study results. 11…”
Section: Discussionmentioning
confidence: 99%